COLLABORATIVE WRITING: ANALYZING STUDENT’S RESPONSES IN WRITING ACTION RESEARCH PROPOSAL - Eni Dwi Lestariningsih; Suparti Suparti; Testiana Deni Wijayatiningsih; Dwi Ampuni Agustina (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
This study aims to analyze the student’s responses in writing action research proposals. The method  of this research is the descriptive quantitative.  The subject of this study was UT Semarang students 2018.1 in Pokjar Kaliwungu Kendal who took Action Research courses. The data collection technique used questionnaires by giving a set of questions or written statements to respondents to answer them. The results of the student’ s responses analysis before and after the Colaborative Writing model application showed that there was an increase in the average student’ s activeness because they were more enthusiastic in writing Classroom Action Research proposals by collaborating in writing with groups according to the developed teaching materials. Their tendency to more easily determine the topic of research using the Collaborative Writing model.Keywords: analyzing, writing research, collaborative writing, student’s responses